2021
DOI: 10.3390/ijerph18115724
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Smartphone Use during the COVID-19 Pandemic: Its Association with Pandemic-Related and Generalized Beliefs

Abstract: Smartphone technologies have played a crucial role in the fight against the COVID-19 pandemic; however, the increased use of smartphones during the pandemic period may expose the general public to a higher risk of problematic smartphone use (PSU). This study aimed to estimate the prevalence of PSU among Chinese community adults and adopted a social-cognitive theory and social axiom framework to evaluate the effects of beliefs on PSU. A Chinese adult sample (N = 616) was obtained through probability sampling vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
3
16
0
1
Order By: Relevance
“…We obtained an unoptimistic incidence of PSU (49.70%) among quarantined medical students, which was higher than that of Chinese senior students (16.4%) from an online survey conducted on February 2020 ( 8 ). Consistent with our results, a cross-sectional study revealed a PSU prevalence of 59.42% in medical students from two provinces in China ( 42 ), and in another study the prevalence was 43.3% among Chinese adults ( 43 ). According to the I-PACE model and CIUT, the high prevalence of PSU among quarantined medical students was related to various factors ( 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…We obtained an unoptimistic incidence of PSU (49.70%) among quarantined medical students, which was higher than that of Chinese senior students (16.4%) from an online survey conducted on February 2020 ( 8 ). Consistent with our results, a cross-sectional study revealed a PSU prevalence of 59.42% in medical students from two provinces in China ( 42 ), and in another study the prevalence was 43.3% among Chinese adults ( 43 ). According to the I-PACE model and CIUT, the high prevalence of PSU among quarantined medical students was related to various factors ( 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…10 The high rate of smartphone addiction among the Bangladeshi students during the COVID-19 pandemic is concerning, as the prior studies have reported substantial consequences related to excessive smartphone use among students. [26][27][28] However, some of the reasons can explain such a higher PSU prevalence rate in the present study. For example, the participants who mandatorily attend online schooling might be responsible, as the previous study reported.…”
Section: Discussionmentioning
confidence: 51%
“…We obtained an unoptimistic incidence of PSU (49.70%) among quarantined medical students, which was higher than that of Chinese senior students (16.4%) from an online survey conducted on February 2020 (8). Consistent with our results, a crosssectional study revealed a PSU prevalence of 59.42% in medical students from two provinces in China (42), and in another study the prevalence was 43.3% among Chinese adults (43). According to the I-PACE model and CIUT, the high prevalence of PSU among quarantined medical students was related to various factors (44).…”
Section: Discussionsupporting
confidence: 80%